Dietary wolfberry upregulates carotenoid metabolic genes and enhances mitochondrial biogenesis in the retina of db/db diabetic mice. Issue 7 (15th March 2013) - Yu, Huifeng; Wark, Logan; Ji, Hua; Willard, Lloyd; Jaing, Yu; Han, Jing; He, Hui; Ortiz, Edlin; Zhang, Yunong; Medeiros, Denis M.; Lin, Dingbo
<x xml:space="preserve">Abstract</x> Scope Our aim was to investigate whether dietary wolfberry altered carotenoid metabolic gene expression and enhanced mitochondrial biogenesis in the retina of diabetic mice. Methods and results Six‐week‐old male db/db and wild‐type mice were fed the control or wolfberry diets for 8 weeks. At study termination, liver and retinal tissues were collected for analysis by transmission electron microscopy, real‐time PCR, immunoprecipitation, Western blot, and HPLC. Wolfberry elevated zeaxanthin and lutein levels in the liver and retinal tissues and stimulated expression of retinal scavenger receptor class B type I, glutathione S‐transferase Pi 1, and β, β‐carotene 9′, 10′‐oxygenase 2, and induced activation and nuclear enrichment of retinal AMP‐activated protein kinase α2 (AMPK‐α2). Furthermore, wolfberry attenuated hypoxia and mitochondrial stress as demonstrated by declined expression of hypoxia‐inducible factor‐1‐α, vascular endothelial growth factor, and heat shock protein 60. Wolfberry enhanced retinal mitochondrial biogenesis in diabetic retinas as demonstrated by reversed mitochondrial dispersion in the retinal pigment epithelium, increased mitochondrial copy number, elevated citrate synthase activity, and upregulated expression of peroxisome proliferator‐activated receptor γ co‐activator 1α, nuclear respiratory factor 1, and mitochondrial transcription factor A. Conclusion Consumption of dietary wolfberry could be beneficial to retinoprotection through reversal of mitochondrial function in diabetic mice.